Profile of sugammadex for reversal of neuromuscular blockade in the elderly: current perspectives - Carron M (Dove Medical Press, 2017)
Michele Carron, Francesco Bertoncello, Giovanna Ieppariello Department of Medicine, Anesthesiology, and Intensive Care, University of Padova, Padua, Italy Abstract: The number of elderly patients is increasing worldwide. This will have a significant impact on the practice of anesthesia in future decades. Anesthesiologists must provide care for an increasing number of elderly patients, who have an elevated risk of perioperative morbidity and mortality. Complications related to postoperative residual neuromuscular blockade, such as muscle weakness, airway obstruction, hypoxemia, atelectasis, pneumonia, and acute respiratory failure, are more frequent in older than in younger patients. Therefore, neuromuscular blockade in the elderly should be carefully monitored and completely reversed before awakening patients at the end of anesthesia. Acetylcholinesterase inhibitors are traditionally used for reversal of neuromuscular blockade. Although the risk of residual neuromuscular blockade is reduced by reversal with neostigmine, it continues to complicate the postoperative course. Sugammadex represents an innovative approach to reversal of neuromuscular blockade induced by aminosteroid neuromuscular-blocking agents, particularly rocuronium, with useful applications in clinical practice. However, aging is associated with certain changes in the pharmacokinetics of sugammadex, and to date there has been no thorough evaluation of the use of sugammadex in elderly patients. The aim of this review was to perform an analysis of the use of sugammadex in older adults based on the current literature. Major issues surrounding the physiologic and pharmacologic effects of aging in elderly patients and how these may impact the routine use of sugammadex in elderly patients are discussed. Keywords: sugammadex, aging, elderly, neuromuscular blockade, rocuronium, anesthesia, safety